Study of the Impact of Climate Change Factors, Management Practices, and Labor Availability on Productivity of Agricultural Resource Management: The Case of Fruit Farmers in Binjai - Adnani Adnani; Dewa Oka Suparwata; Winarto Ramlan; Nurhayati Nurhayati (West Science Agro, 2023)
Climate change poses significant challenges to agricultural systems, affecting productivity and sustainability. This study investigates the impact of climate change factors, management practices, and labor availability on agricultural resource management productivity among fruit farmers in Binjai. A sample of 121 farmers was surveyed, and data were analyzed using IBM SPSS. Results indicate a 1.5°C temperature increase over the past decade, negatively correlating with crop yields. Diverse management practices were observed, with integrated pest management positively influencing productivity. Labor availability exhibited seasonal variations, influenced by migration patterns. Spatial analysis highlighted temperature-sensitive clusters and regions prone to extreme weather events. The findings provide actionable insights for tailored interventions, emphasizing the need for climate-resilient strategies in Binjai's fruit farming.